Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 13325 species occurrences available in GBIF matching the query: { "DatasetKey" : [ "is Herbier du Bénin" ] } The dataset includes 13325 records from 1 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0013859-160311141623029/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences